Evaluation of Stress Perception, Social Competence and Result Expectation of Senior Nursing Students - Müjgan Solak; Sevcan Topçu; Zuhal Emlek Sert (Ahi Evran Medical Journal)
Purpose: This study was conducted to determine the stress perceptions and social competence and outcome expectation levels of senior nursing students and to examine the relationship between stress perceptions and social competence outcome expectation levels.